2007
DOI: 10.1080/15622970600960207
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of lymphocytes in schizophrenia

Abstract: The data suggest that the excess of LB in schizophrenic patients is associated with the dysfunction of energy metabolism in LAL, and these abnormalities are related to schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Mononuclear cells of SZ patients had enlarged mitochondria with fragmented cristae, which was independent of antipsychotic drug type used (Inuwa et al, 2005). In a similar study, activated lymphocytes in individuals with SZ had a lower mitochondrial density than controls (Uranova et al, 2007).…”
Section: Morphological and Physiological Changes In Mitochondria In Pmentioning
confidence: 84%
“…Mononuclear cells of SZ patients had enlarged mitochondria with fragmented cristae, which was independent of antipsychotic drug type used (Inuwa et al, 2005). In a similar study, activated lymphocytes in individuals with SZ had a lower mitochondrial density than controls (Uranova et al, 2007).…”
Section: Morphological and Physiological Changes In Mitochondria In Pmentioning
confidence: 84%
“…15 The heteromeric signaling complex, resulting from binding of TGF-β1 to type II receptor and in turn type I receptor, transduces signals through receptor-regulated Smads (Smad2/3) and common-partner Smad (Smad4), leading to transcriptional regulation of target genes. A number of non-canonical TGF-β signaling pathways have also been identified, including the rho-like guanosine triphosphatases, 16,17 PI3K/Akt, 1821 and the mitogen-activated protein kinases (MAPKs), namely extracellular signal-regulated kinase 1/2, 22,23 c-Jun N-terminal kinase (JNK), 2426 and p38 MAPK.…”
Section: Introductionmentioning
confidence: 99%
“…One study found differences in the genotypic distribution of a functional polymorphism of manganese superoxide dismutase, thought to protect mitochondria from reactive oxygen species, among several DSM‐IV subgroups of SZ, including SZP (Akyol et al,2005). In another study, lymphocytes analyzed from paranoid schizophrenia patients and controls showed less mitochondrial volume in the patients in certain types of lymphocytes (Uranova et al,2007). Moreover, the severity of the mitochondrial deficit was positively correlated with symptom severity, linking paranoid symptoms with mitochondrial impairment, albeit in blood (Uranova et al,2007).…”
Section: Discussionmentioning
confidence: 95%
“…In another study, lymphocytes analyzed from paranoid schizophrenia patients and controls showed less mitochondrial volume in the patients in certain types of lymphocytes (Uranova et al,2007). Moreover, the severity of the mitochondrial deficit was positively correlated with symptom severity, linking paranoid symptoms with mitochondrial impairment, albeit in blood (Uranova et al,2007). A decrease in mitochondrial number could therefore be associated with the symptoms of paranoia.…”
Section: Discussionmentioning
confidence: 95%